Re-examining Pre-service EFL Teachers’ Readiness for Technology Integration: A TPACK Analysis in the Indonesian Context - Asmi Rusmanayanti; Rusmansyah Rusmansyah; Nasrullah Nasrullah; Arief Ertha Kusuma (Vidya Karya, 2026)
The rapid expansion of digital technologies in education has renewed scholarly interest in how teachers conceptualize and enact technology integration. The Technological Pedagogical Content Knowledge (TPACK) framework provides a theoretically robust lens to comprehend the interconnected interaction among technology, pedagogy, and disciplinary knowledge. This study investigates Indonesian pre-service English as a foreign language (EFL) teachers’ self-perceived TPACK competencies and their readiness to integrate technology into future instructional practice. Using a quantitative design, a validated TPACK questionnaire was administered to 100 pre-service teachers. The findings demonstrated a familiar yet theoretically significant pattern: participants report strong technological knowledge but comparatively weaker pedagogical, content, and pedagogical-content knowledge. This imbalance suggests that technological familiarity alone does not translate into integrated professional competence. The study argues that TPACK development must be understood as a situated, iterative process shaped by institutional structures, epistemic beliefs, and disciplinary demands. Implications are offered for redesigning teacher education curricula to foreground epistemic integration rather than tool-centered training.